Control of swarm behavior for a batteryless and sensorless small jumping robot using wireless power supply. (17th January 2023) - Miyashita, Tomoki; Takuma, Takashi
Abstract : This paper proposes a method to control small jumping swarm robots without a sensor, computer, or battery. For activation without a battery, the robots received power from a wireless power supply source. To control the direction of movement of the swarm robots, the frequency of the power supply was locally varied. The experiments revealed that the robots tended to gather at specific locations although their individual destinations are not specifically controlled. GRAPHICAL ABSTRACT: UF0001